2012
DOI: 10.1007/s13365-012-0123-0
|View full text |Cite
|
Sign up to set email alerts
|

Human trigeminal ganglionic explants as a model to study alphaherpesvirus reactivation

Abstract: Varicella zoster virus (VZV) latency is characterized by limited virus gene expression and the absence of virus DNA replication. Investigations of VZV latency and reactivation have been hindered by the lack of an in vitro model of virus latency. Since VZV is an exclusively human pathogen, we used naturally infected human trigeminal ganglia (TG) obtained at autopsy to study virus latency. Herein, we report optimization of medium to maintain TG integrity as determined by histology and immunohisto-chemistry. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…There is one report of VZV reactivation from human ganglia that had been removed 1-5 days post-mortem (Saitoh et al, 2013), but this observation has not been confirmed. Furthermore, only minimal amounts of VZV DNA replication, presumably an event preceding virus reactivation, have been demonstrated within this time frame (Azarkh et al, 2012).…”
Section: During Latency Hsv-1 and Vzv Gene Transcription Is Restrictedmentioning
confidence: 85%
See 2 more Smart Citations
“…There is one report of VZV reactivation from human ganglia that had been removed 1-5 days post-mortem (Saitoh et al, 2013), but this observation has not been confirmed. Furthermore, only minimal amounts of VZV DNA replication, presumably an event preceding virus reactivation, have been demonstrated within this time frame (Azarkh et al, 2012).…”
Section: During Latency Hsv-1 and Vzv Gene Transcription Is Restrictedmentioning
confidence: 85%
“…Following animation, HSV-1 gene transcription undergoes a shift from generalized to organized transcription that orchestrates protein synthesis with DNA replication resulting in release of progeny infectious virus by 24 h for HSV-1. To date, VZV reactivation with release of infectious virus from human ganglia explants has not been demonstrated, but VZV DNA replication has been detected by quantitative PCR analysis of human ganglia explants (Azarkh et al, 2012). Lower-right graph: y-axis, HSV-1 DNA copy number (black line) and VZV DNA copy number (red line); x-axis, time the human ganglia explants were incubated in optimized culture medium; data represent mean¡SEM for virus DNA quantification by real-time, TaqMan-based PCR.…”
Section: Alphaherpesvirus Gene Transcription Is Deregulated During VImentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we focused our present analyses on adult human trigeminal ganglia (TG), where both HSV-1 and VZV are latent (Cohrs et al 2005). Previously, both HSV-1 and VZV DNA replication was observed in human TGs cut into equal pieces and cultured for 0, 1 and 5 days (Azarkh et al 2012). However, latent HSV-1 and VZV DNA are not uniformly distributed in human TG (Cohrs et al 2005; Hüfner et al 2009) and a more accurate analysis of virus DNA replication in human TG requires confirmation that dissociated ganglia are randomly distributed among multiple samples.…”
Section: Introductionmentioning
confidence: 99%
“…TG were washed and mechanically dissociated. Cells were collected (1000 g , 10 min, 4°C), resuspended in 3 ml of complete culture medium #2 lacking anti-mitotic drugs (Azarkh et al 2012) and distributed into 7 wells in each of three 96-well poly-L-ornithine/laminin-coated plates (BD-Biocoat, Fisher Biosciences, Vacaville, CA). Cells were not sorted before use and contained neurons, satellite cells, which enhance neuronal survival (Hanai et al 2011), and other non-neuronal cells.…”
Section: Introductionmentioning
confidence: 99%